<h3>
Answer: G) -2</h3>
=======================================================
Explanation:
I'm assuming you meant to say (a+y)^2 + 2y
Replace each copy of 'a' with 5. Replace each copy of 'y' with -3. Use PEMDAS to simplify.
(a+y)^2 + 2y
(5 + (-3))^2 + 2(-3)
(5-3)^2 + 2(-3)
(2)^2 + 2(-3)
4 + 2(-3)
4 - 6
-2
So (a+y)^2 + 2y = -2 when a = 5 and y = -3.
4.15, 6.3, 8.45, 10.6, 12.75
You just subtract 4.15 from 6.3 and you get a difference of 2.15. Then you add it to 8.45 giving you the answer of 10.6 and then you add 2.15 to that getting 12.75.
Answer:
D is the correct answer
Step-by-step explanation:
first you subtract the 3 from the left side and add it to the right side. then you divide both side by negative 3 and flip the less than sign to a greater than sign
1.20*2 = 2.40 + 0.60 = 3.00
1.20 + 0.60 = 1.80
1.20 per egg and 0.60 for toast
1st answer